Characterization of Mckibben Pneumatic artificial muscle - Renung Kinanthi. (2013)
McKibben Muscle, also known as Pneumatic Artificial Muscle, is widely used today. Its characteristic compliance and versatility makes it suitable for various uses ranging from hard-duty industrial use to mimicking human muscle.